Combined Effect of Nanoparticles and Leuconostoc mesentroides ssp. cremoris Bacteriocin against Listeria monocytogenes Isolated from Locally Soft Cheese - Nibras Nazar Mahmood (Journal of Global Pharma Technology, 2016)
Listeria monocytogenes has been as important opportunistic bacteria for human since 1929 and as food borne pathogenic bacteria since 1981.  Out of Twenty samples of locally soft cheese, only two isolates of Listeria monocytogenes were isolated and identified using microscopically, cultural and biochemical methods. The isolates were multi drug resistant to ceftriaxone ,trimethoprime amoxicillin ,aztreoname, ciprofloxacin and penicillin. While, these isolates were sensitive to Ampicilin, imipenem, and azithromycin. The antilisterial activity of 400 µg/ml of both silver and zinc Nanoparticles and bacteriocin of L. mesentroides ssp. cremoris in soft cheese for 24 h. was evaluated. The results showed that bacteriocin, silver nanoparticles and zinc nanoparticles reduced the growth of L.monocytogenes in cheese with inhibition percent (49.48, 19 .38, 38.14) % respectively .The combination between bacteriocin with nanoparticles (1:1) showed increased in the reduction of L.monocytogenes growth with (58.76 and 67.01) % for bacteriocin with silver nanoparticles and bacteriocin with zinc nanoparticles respectively. These results indicate that the combination of bacteriocin with nanoparticles has a protective effect against   Listeria monocytogenes in locally soft cheese Keywords: Leuconostoc mesentroides; Cheese; Listeria monocytogenes; Nanoparticles.